PENGARUH PEMBERIAN NUTRISI DENGAN TAMBAHAN PUPUK SUSULAN PADA AWAL WAKTU YANG BERBEDA TERHADAP PERTUMBUHAN spirulina sp. - Firdaus, Alfa Aulia; Yuniar, Is; Nuhman (FISHERIES Jurnal Perikanan dan Ilmu Kelautan, 2021)
The purpose of this study was to determine the effect of providing nutrients with additional fertilizers at the beginning of different times on the growth of Spirulina sp. This research was conducted in December 2020 at the Hangtuah University Laboratory. This study used a one factorial completely randomized design (CRD) method consisting of 5 treatments and 5 replications, namely A = no supplementary fertilizers, B = supplementary fertilizers on day 3 at a dose of 0.5 ml / L, C = administration supplementary fertilizer on day 4 at a dose of 0.5 ml / L, D = supplementary fertilizer on day 5 at a dose of 0.5 ml / L, E = supplementary fertilizer on day 6 at a dose of 0.5 ml / L . The results of the kruskal wallis test showed that there was no effect of giving nutrients with additional fertilizers at the beginning of different times on the growth of Spirulina sp. The ANOVA results show that there is an effect of providing nutrients with additional fertilizers at the beginning of different times on the daily growth rate of Spirulina sp.